Phase I study of ribociclib (CDK4/6 inhibitor) with spartalizumab (PD-1 inhibitor) with and without fulvestrant in metastatic hormone receptor-positive breast cancer or advanced ovarian cancer - Sara M Tolaney; Tianyu Li; Elizabeth A Mittendorf; Geoffrey I Shapiro; Stephanie K Dougan; Nabihah Tayob; Joyce F Liu; Khanh Do; Heather Parsons; Molly DiLullo; Eileen Wrabel; Lestat R Ali; et al. (Journal for ImmunoTherapy of Cancer)
Background Preclinical evidence suggests that cyclin-dependent kinases 4 and 6 (CDK4/6) inhibitors enhance antitumor immunity. We conducted a phase I trial of ribociclib (CDK4/6 inhibitor) plus spartalizumab (PD-1 inhibitor) in patients with hormone receptor (HR)-positive/HER2-negative metastatic breast cancer (MBC) or advanced ovarian cancer (AOC). The combination was also evaluated with fulvestrant in MBC.Methods In Cohort A, ribociclib was administered on Days 1–21 (28-day cycle) starting at 400 mg, and spartalizumab at 400 mg on Day 1. Dose escalation was followed by expansion in AOC. Fulvestrant was added (Cohort B) with a safety run-in followed by expansion in MBC. Primary objectives were to determine the maximum tolerated dose (MTD) and recommended phase 2 dose (RP2D), and safety and tolerability of the combinations.Results 33 patients enrolled (n=18, Cohort A; n=15, Cohort B). The RP2D of ribociclib in both cohorts was 600 mg. Treatment-related adverse events in >20% of patients in either cohort were neutropenia, fatigue, anemia, thrombocytopenia, hypertransaminasemia, maculopapular rash, fatigue, and nausea. Hypertransaminasemia occurred in 66.7% (AST) and 46.7% (ALT) of patients in Cohort B, including 46.7% and 40.0%, respectively, of grade 3 or 4 events. Two confirmed partial responses were observed (13.3%) in Cohort B, in patients with low baseline serum thymidine kinase activity, coupled with an increase on-treatment. Peripheral blood flow cytometry across patients demonstrated on-target drug binding with increases in PD-1 occupancy and activated CD8+ T cells during treatment, irrespective of response. PD-L1-positivity, tumor-infiltrating lymphocytes, or tumor mutational burden did not correlate with progression-free survival (PFS). Several copy-number variations detected with next-generation sequencing correlated with PFS.Conclusions Ribociclib with spartalizumab and fulvestrant showed limited efficacy and elevated hepatotoxicity, precluding further development. Correlative analyses revealed treatment-induced immunological effects, and genomic alterations associated with PFS.